1968
DOI: 10.3758/bf03331581
|View full text |Cite
|
Sign up to set email alerts
|

The influence of word-knowledge on the word-frequency effect in recognition memory

Abstract: The influence of word-knowledge on the word-frequency effect in recognition memoryThe signal detection theory technique of using ope rating characteristics (OCs) in the study of recognition memory is derived from S's confidence ratings made to a test sequence of words containing both initial inspection and additional items (see, for example, Green & swets, 1966, for details). This method provides a graphic estimate, ds , of the degree of difficulty in discriminating new from old words. As part of one such appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1
1

Year Published

1970
1970
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 1 publication
(1 reference statement)
1
22
1
1
Order By: Relevance
“…3 These data show the same pattern of results as that reported by Allen and Garton (1968). First, recognition ofzero-frequency CS-tech items was significantly'[ higher for computer science students than for psychology students [F(l,70) = 14.43,MS e = .32],similartothesuperi or recognition of physics words by physics students in Allen and Garton's study.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…3 These data show the same pattern of results as that reported by Allen and Garton (1968). First, recognition ofzero-frequency CS-tech items was significantly'[ higher for computer science students than for psychology students [F(l,70) = 14.43,MS e = .32],similartothesuperi or recognition of physics words by physics students in Allen and Garton's study.…”
Section: Resultssupporting
confidence: 74%
“…The present study is based on the naturalistic approach used by Allen and Garton (1968). The advantage of this approach is that between-group differences in preexperimental familiarity occur naturally, and because the same materials are used for both groups, there is no confounding ofstructural word characteristics and word frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is dear, then, that rare words, although harder to recall, are easier to recognize than common words. What is also apparent is that their greater distinctiveness cannot depend entirely on their more specialized meanings (but see Allen & Garton, 1968), since so many rare words in the present study were totally unfamiliar ones, e.g., "pagrus" and "zabeta." Now, it can be shown that rare words differ significantly in structure from common words, for instance, in their greater incidence of u n usual digrams.…”
Section: Resultsmentioning
confidence: 60%
“…One of the most interesting paradoxes in memory research is the finding that if retention is tested by means of a recall test, high-frequency (HF) words are generally recalled more accurately than low-frequency (LF) words (e.g., Deese, 1960;Sumby, 1963), whereas on a recognition test, it is LF words that are most accurately designated as having been seen before (e.g., Allen & Garton, 1968;Glanzer & Bowles, 1976;Gorman, 1961;Underwood & Freund, 1970). It is puzzling that such different results are evident when retention of the same material is assessed via different tests.…”
mentioning
confidence: 99%